O Pewnym Zagadnieniu Quasi – Ustalonym Termosprężystości dla Tarczy Kołowej - Piechocki, W. (Engineering Transactions, 1960)
A solution for a circular disc acted on by time-variable heat sources isgiven. The problem is treated as quasi-steady-state, that is the inertia terms in the equations of elasticity are rejected. Free and clamped edge conditions are considered.To satisfy the edge conditions, the stress function and the displacement vector are used. All the elastic quantities are expressed in the form of a series of BESSEL functions of the first kind.